The economic benefits of VET for inidividuals - (:unkn) unknown (Publications Office of the European Union, 2011)
"This report examines the economic return on vocational education and training (VET) for individuals across the EU. The benefits analysed are the private ones that accrue to individuals who receive training. We find that returns on secondary (but non-tertiary) initial VET are of the same order of magnitude as those characterising tertiary general education. These benefits are in terms of earnings and the probability of being in employment. The methodology involves econometric analysis of large comparable data sets drawn from across the EU. Some attention is given to the problem of establishing the causal effect of VET. In addition to considering the overall impact of training, as far as the data allows, the report attempts to distinguish between initial VET, academic education and continuing VET. An important focus of the research is to investigate the extent to which continuing training complements initial VET (the 'skills beget skills' hypothesis), rather than the conventional view of training compensating for low levels of initial education." (Hrsg., BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; S 4.3.3 Effizienz & Effektivität des Berufsbildungswesens; S 4.3.6 Human Capital; G 1.3.3.1 Qualifikationsverwertung; I 2.2 Europa; Berufsausbildung; Kosten-Nutzen-Analyse; Humankapital; Ausbildungsertrag; Einkommenseffekte; Soziale Faktoren; Europa